Pengaruh Pelapisan Emulsi Minyak Wijen dan Minyak Sereh terhadap Mutu dan MasaSimpan Buah Jeruk Siam (Citrus nobilis Lour) - Andri Frans Kalvin Gurning; I Made Supartha Utama; Ni Luh Yulianti (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2019)
The purpose of this research is knowing the influence of different consentration mixture between sesame and citronella oil in water as coating material on the quality of citrus fruits during storage at room temperature. Consentration sesame oil emulsion varied 0%, 0.5%, and 1% in citronella oil combination 0%, 0.5%, 1% and 1.5%. The additional ingredients used to make emulsions were 1% of tween 80, 0.5% oleic acid, and 3% alcohol. Untreatment control fruit was also prepared for comparison. The experiment was conducted using a Completely Randomized Design (CRD) with three replications. The results showed that the treatment of sesame and citronella oil significantly affected the quality and storage period of citrus fruits. The combined concentration of 0.5% sesame oil and 0.5% citronella oil provides the best results which can reduce weight loss, decay damage, pH alteration and total dissolved solids of fruit juice, and fruit hardness.